The Martinsburg Initiative: A Collaboration Between Public Safety, Public Health, and Schools to Address Trauma and Substance Use. Issue 6 (November 2022) - Wisdom, April C.; Villamil, Vanessa; Govindu, Madhumita; Kursey, Margaret; Peppard, Lora; Bates, Rebecca A.; Myrick, Amie; Snyder, Caroline; Noonan, Rita K.
Abstract : The Martinsburg Initiative (TMI) is a community-based model developed in Martinsburg, West Virginia, that implements a comprehensive approach to adverse childhood experiences and substance use prevention and mitigation by leveraging partnerships in public health and health care, public safety, and education. TMI receives coordinated federal funding and technical assistance from the Centers for Disease Control and Prevention, the Washington-Baltimore High Intensity Drug Trafficking Agency, and the National Association of County and City Health Officials to integrate evidence-based and promising strategies. It advances such strategies by translating them for implementation within the community, evaluating the reach and potential impact of the model, and by engaging key stakeholders. Preliminary results describing program reach and short-term outcomes collected for a subset of the interventions during implementation are presented. The model uses touchpoints across multiple community sectors in the city of Martinsburg to break the cycle of trauma and substance use across the life span.